2022
DOI: 10.1088/1748-9326/ac4cf2
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of temperature and relative humidity for growth of COVID-19 cases and death rates

Abstract: Akin to respiratory tract infection diseases, climatic conditions may significantly influence the COVID-19 epidemic. Since the beginning of the COVID-19 pandemic, significant efforts have been made to explore the relationship between climatic condition and growth in number of COVID-19 cases. Contentious findings of either positive, negative, or no association with climatic conditions have been reported in many studies based on some early data on COVID-19 cases over a shorter time span. We integrate COVID-19 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Thus both temperature and humidity seem to play important roles in the regulation of COVID-19 growth. Not only the individual effect of temperature and relative humidity, but also their joint effects are found significant mimicking the existence of nonlinear relationship between growth of COVID-19 epidemic and meteorological covariates ( Khan, Abedin, Khan, et al, 2022 , Biryukov et al, 2020 ). Though lower degree associations with some other climatic factors such as air drying capacity, wind speed, and precipitation are explored, government intervention is found to be more important for suppression of transmission ( Sera et al, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 77%
See 1 more Smart Citation
“…Thus both temperature and humidity seem to play important roles in the regulation of COVID-19 growth. Not only the individual effect of temperature and relative humidity, but also their joint effects are found significant mimicking the existence of nonlinear relationship between growth of COVID-19 epidemic and meteorological covariates ( Khan, Abedin, Khan, et al, 2022 , Biryukov et al, 2020 ). Though lower degree associations with some other climatic factors such as air drying capacity, wind speed, and precipitation are explored, government intervention is found to be more important for suppression of transmission ( Sera et al, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 77%
“…Though public compliance and behavioral responses to stringent policies regulate the transmission of virus, droplets and surface transmissions can be regulated by the environmental factors such as temperature and relative humidity ( Biryukov et al, 2020 , Xie & Zhu, 2020 ). Thus the growth of COVID-19 epidemic can be regulated by any human intervention that reduces human-to-human contact and by natural phenomena through a complex interaction of meteorological covariates ( Khan, Abedin, Khan, et al, 2022 , Biryukov et al, 2020 , Bashir et al, 2020 ). This study explores the interactions of temperature and relative humidity for the prediction of growth of COVID-19 epidemic and utilizes this prediction for monitoring the progress towards the planned control.…”
Section: Introductionmentioning
confidence: 99%
“…External factors (such as temperature, humidity, and available resources) may cause the spread of COVID-19 to accelerate or slow down and switch between two or more regimes [11] , [12] , [13] . Therefore, in this article, we suppose that the transmission rate in model (2.2) is driven by the semi-Markov process and the Gaussian white noise.…”
Section: Preliminaries and Modelmentioning
confidence: 99%
“…The results of Khan et al. [13] showed that temperature and relative humidity together affect the propagation of COVID-19. Alqudah et al.…”
Section: Introductionmentioning
confidence: 99%
“…by making time invariant factors (corruption, population density, etc.) insignificant [21,22]. Consequently, sprouting different variants of SARS-CoV-2 (Delta, Alpha, and Omicron) over time is infusing more heterogeneity in data.…”
Section: Data Processing and Integrationmentioning
confidence: 99%